From the rugby field to the dance floor: a narrative case study of Ilona Maher’s negotiation of femininity while competing on Dancing with the Stars - de Seriere, Dominique (My University, 2025)
This qualitative research proposal explores the negotiation of femininity that non-traditional female sports athletes experience. This thesis is an investigation of how U.S Women’s Rugby Olympian Ilona Maher performs her femininity as a negotiation strategy during her time competing on the television show Dancing with the Stars. Through a narrative case research method, this study focuses on analyzing the discourse surrounding Maher’s experiences on DWTS through the social media content that she posted regarding her time on the show and aired episodes of DWTS. The study provides a deeper contribution to discussions surrounding gender performance, self-representation, negotiation, and the intersection of media, athletic sports, and femininity through a societal lens.
Keywords: Gender performance; Self-representation; Negotiation; Intersection of media, athletic sports, and femininity